Dead Rescuers: The Commemoration of Poles Who Lost Their Lives Saving Jews During the Second World War - Łysak, Tomasz (Porównania, 2023)
After their electoral victory in 2015, the Law and Justice party started a counter-revolution in historical policy, intended to undermine critical historiography on the Holocaust. As a result, “dead rescuers,” Poles who lost their lives saving Jews during the Second World War, are commemorated by a host of institutions: a government-sponsored research institute, museums, and the Catholic Church. This commemoration borrows its aesthetics from earlier practices established in Holocaust memory: post-traumatic architecture, lists of victims, and micro-history to boost national pride and defend the good name of Poland abroad. Memory actors receive financial support from the government, becoming a mouthpiece for its reclaiming of the past for ethnonationalist ends.